DTI of tuber and perituberal tissue can predict epileptogenicity in tuberous sclerosis complex. (8th December 2015) - Yogi, Akira; Hirata, Yoko; Karavaeva, Elena; Harris, Robert J.; Wu, Joyce Y.; Yudovin, Sue L.; Linetsky, Michael; Mathern, Gary W.; Ellingson, Benjamin M.; Salamon, Noriko
Abstract : Objective: To evaluate whether diffusion tensor imaging (DTI) can predict epileptogenic tubers by measuring apparent diffusion coefficient (ADC), fractional anisotropy, axial diffusivity, and radial diffusivity in both tubers and perituberal tissue in pediatric patients with tuberous sclerosis complex (TSC) undergoing epilepsy surgery. Methods: We retrospectively selected 23 consecutive patients (aged 0.4–19.6 years, mean age of 5.2; 13 female, 10 male) who underwent presurgical DTI and subsequent surgical resection between 2004 and 2013 from the University of California–Los Angeles TSC Clinic. We evaluated presurgical examinations including video-EEG, brain MRI, 18 F-fluorodeoxyglucose–PET, magnetic source imaging, and intraoperative electrocorticography for determining epileptogenic tubers. A total of 545 tubers, 33 epileptogenic and 512 nonepileptogenic, were identified. Two observers generated the regions of interest (ROIs) of tubers (ROI tuber ), the 4-mm-thick ring-shaped ROIs surrounding the tubers (ROI perituber ), and the combined ROIs (ROI tuber+perituber ) in consensus and calculated maximum, minimum, mean, and median values of each DTI measure in each ROI for all tubers. Results: The Mann–Whitney U test demonstrated that the epileptogenic group showed higher maximum ADC and radial diffusivity values in all ROIs, and that maximum ADC in ROI tuber+perituber showed the strongest difference ( p = 0.001). Receiver operating characteristic analysis demonstrated that maximum ADC measurements in ROI tuber+perituber (area under curve = 0.68 ± 0.05, p < 0.001) had 81% sensitivity and 44% specificity for correctly identifying epileptogenic tubers with a cutoff value of 1.32 μm 2 /ms. Conclusions: DTI analysis of tubers and perituberal tissue may help to identify epileptogenic tubers in presurgical patients with TSC more easily and effectively than current invasive methods.